2006
DOI: 10.1002/uog.3871
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between prenatal ultrasound and autopsy findings: a study of second‐trimester abortions

Abstract: Objective To evaluate discrepancies between sonographic and autopsy findings following termination of pregnancy (TOP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 27 publications
0
46
3
1
Order By: Relevance
“…One false-positive US diagnosis of renal aplasia has been reported in a case of oligohydramnios similar to one of our cases. 4 Akgun et al 3 and Kaasen et al 7 have reported false-positive diagnosis of associated …”
Section: Discussionmentioning
confidence: 97%
“…One false-positive US diagnosis of renal aplasia has been reported in a case of oligohydramnios similar to one of our cases. 4 Akgun et al 3 and Kaasen et al 7 have reported false-positive diagnosis of associated …”
Section: Discussionmentioning
confidence: 97%
“…OF D&E SPECIMENS There are several studies 18,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] that have reviewed the correlation between prenatal ultrasound and autopsy findings, all based on examination of intact fetuses. Agreement between prenatal ultrasound findings and autopsy diagnosis when autopsy is performed on an intact fetus ranges from 45% to 91.2%.…”
Section: Value Of Careful Examinationmentioning
confidence: 99%
“…However, more recent studies have demonstrated that increased efficacy of prenatal ultrasound diagnosis resulted in more efficient planning for correction, immediate neonatal care and decreased hospital admissions. 6,11,20 Our results show increased efficacy (73.6%) of prenatal diagnosis of GI anomalies, which provided the opportunity to plan for anomalous births and postpartum intervention. Presently, 2D ultrasound is the most used modality in prenatal screening for anatomical development and con genital anomalies.…”
mentioning
confidence: 62%